Peran Orang Tua Tunggal (Single Parent) dalam Menanamkan Nilai-nilai Moral pada Kaum Muda di Rayon Tanjung Morawa - Kurniadi, Benediktus Benteng; Sinaga, Serepina Kristiani (Universitas Batanghari Jambi, 2024)
This research aims to determine the role of single parents in Catholic families and determine the moral values of young people in Tanjung Morawa Rayon. This research uses a qualitative approach with observation, interview and documentation techniques. The number of respondents in the research was 14 people, namely 7 single parents and 7 young people in Tanjung Morawa Rayon. Based on the research results, it was found that the role of single parents plays a role well and also significantly in the moral values of young people which shape young people into individuals who have integrity, good manners, responsibility and strong discipline. Single parents not only provide instructions, but also provide real examples in daily life, reinforcing these values through direct interaction and active participation in church activities.